The Effects of Non-Nutritive Sweetener Consumption in the Pediatric Populations: What We Know, What We Don’t, and What We Need to Learn - Shum, Betty; Georgia, Senta (Frontiers in Endocrinology, 2021)
Childhood obesity is increasing at an alarming rate in the United States. This trend carries serious risk of children developing obesity-related diseases including Type 2 diabetes and cardiovascular disease. Non-nutritive sweeteners (NNS) are used as substitution for table sugar as a way to prevent weight gain. Their consumption is ubiquitous in adults and children; however the long-term health outcomes of chronic NNS consumption in children are unclear. Conflicting observational studies suggest that children consuming NNS are at risk for obesity and development of type 2 diabetes, while others concluded some benefits in weight reduction. Here, we review the physiological mechanisms that can contribute to the negative metabolic effects of NNS. We will focus on how NNS alters the sweet perception leading to increase caloric consumption, how NNS alters the gut microbiota, and how NNS may disrupt glucose homeostasis and initiate a vicious cycle of pancreatic endocrine dysfunction. Studies focused on the pediatric population are limited but necessary to determine whether the potential weight loss benefits outweigh the potential negative metabolic outcomes during this critical developmental period.